Impact of COVID-19 on clinical and academic urological uractice: a survey from European Association of Urology Section of Uro-technology - Heinze, Alexander; Umari, Paolo; Basulto-Martínez, Mario; Suarez-Ibarrola, Rodrigo; Liatsikos, Evangelos; Rassweiler, Jens; Guven, Selcuk; Gözen, Ali Serdar (European urology open science, 2020)
Background - The unexpected coronavirus disease 2019 (COVID-19) pandemic has spread worldwide rapidly, developing into a global health crisis. At the same time, it has seriously impacted the daily activities in all the fields of urology. - Objective - To better understand the impact of the COVID-19 pandemic on clinical, academic, and scientific activities as well as on the quality of life of urologists from the main centers in Europe. - Design, setting, and participants - We conducted a survey using a 37-item questionnaire. The survey included three main sections: clinical practice, academic/scientific activities, and personal/social quality of life. - Outcome measurements and statistical analysis - A descriptive analysis was performed using the collected data. - Results and limitations - A total of 107 representatives affiliated to different centers from 22 countries completed the survey. Clinical activities were affected in 54.2% of the centers, and 85.0% of the elective surgeries were cancelled. Of the urological departments, 64.5% were still performing minimally invasive surgery for malignant disease. In 33.6% of the hospitals, dedicated and specially equipped operating theaters for COVID-19-positive patients were not available. According to 72.9% of participants, COVID-19 had a substantial negative impact on academic activities, and 82.3% of the respondents agreed that their quality of life has been affected negatively by the pandemic. Finally, 92.5% of the participants believe that the pandemic will have a moderate to severe impact on the health system of their countries. - Conclusions - Data collected in this survey provide insight into changes brought about in clinical and academic settings amid COVID-19. Along with shortages such as bed occupancy and personal protective equipment, it highlights negative impacts on academic and scientific activities, including the personal and social life of urologists. - Patient summary - It is essential to understand the impact of the coronavirus disease 2019 (COVID-19) pandemic on clinical, academic, and scientific urological activities, as well as on related personal and social issues.
Gesehen am 26.11.2020